Molecules-mediated bidirectional interactions between microbes and human cells - Shengbo Wu; Xueying Bu; Danlei Chen; Xueyan Wu; Hao Wu; Qinggele Caiyin; Jianjun Qiao (npj Biofilms and Microbiomes)
Abstract Complex molecules-mediated interactions, which are based on the bidirectional information exchange between microbes and human cells, enable the defense against diseases and health maintenance. Recently, diverse single-direction interactions based on active metabolites, immunity factors, and quorum sensing signals have largely been summarized separately. In this review, according to a simplified timeline, we proposed the framework of Molecules-mediated Bidirectional Interactions (MBI) between microbe and humans to decipher and understand their intricate interactions systematically. About the microbe-derived interactions, we summarized various molecules, such as short-chain fatty acids, bile acids, tryptophan catabolites, and quorum sensing molecules, and their corresponding human receptors. Concerning the human-derived interactions, we reviewed the effect of human molecules, including hormones, cytokines, and other circulatory metabolites on microbial characteristics and phenotypes. Finally, we discussed the challenges and trends for developing and deciphering molecule-mediated bidirectional interactions and their potential applications in the guard of human health.